Characterizing Suicidal Ideation in Treatment-Resistant Depression Using Neuroimaging - Burhunduli, Patricia (Université d'Ottawa / University of Ottawa, 2020)
Neuroimaging studies have revealed the involvement of subcortical regions in the aetiology of suicide attempts (SA), suicidal behaviours (SB) and depression. What is lacking in the literature is structural evidence of the neurobiological underpinnings of suicidal ideation (SI). The primary aim of this thesis was to identify structural brain imaging correlates associated with SI severity in patients with treatment-resistant major depressive disorder (MDD). The secondary aim of the thesis was to conduct an exploratory analysis to investigate the relationship between depression severity and total hippocampus and hippocampal subfield volumes. Since previous studies have identified hopelessness as a strong predictor of SI, the third aim of the thesis was to determine whether hopelessness was a significant predictor of SI severity. Twenty-nine outpatients with treatment-resistant MDD underwent a single session MRI scan. T1-weighted structural images were collected on a 3T Siemens MR-PET system using a multi-echo magnetization-prepared rapid gradient echo (MPRAGE) protocol. Cortical reconstruction and segmentation were performed using FreeSurfer-6.0.0. Participants underwent clinical interviews in which the severity of SI and depressive symptoms were assessed using the Columbia Suicide Severity Rating Scale (C-SSRS) and the Montgomery-Asberg Depression Rating Scale (MADRS), respectively. Structural brain correlates associated with SI were assessed and preliminary results in our sample (N=29) showed that increased volume and thickness were found in several ROIs with increased SI severity. Hopelessness was strongly correlated with self-rated SI, although not clinician-rated SI. In regard to depression severity, increased depression severity was correlated with decreased total hippocampal volume and decreased in two hippocampal subfields (left cornus ammonis 1 (CA1) (r=0.43, p=0.03) and left molecular layer (r=0.43, p=0.03). The observations of larger volumes and cortical thickness in subcortical regions in relation to SI severity highlight the involvement of ii structural brain abnormalities in suicide. In addition, results showed smaller total hippocampal volume with increased depression severity consistent with previous reports. Different hippocampal subfields may be involved in this association. Further research is required to confirm these findings and to investigate additional regions of interest (ROIs).
Keywords: Structural magnetic resonance imaging; Suicidal ideation; Treatment-resistant depression; Major depressive disorder; Hippocampal subfields; Hopelessness